Investigation of the relationship between virulence factors and genotype of Candida spp. isolated from blood cultures - Fatma Mutlu Sariguzel; Elife Berk; Ayse Nedret Koc; Hafize Sav; Gonca Demir (Journal of Infection in Developing Countries)
Introduction: The aim of study was to investigate the virulence factors of phospholipase, proteinase, esterase production and biofilm formation in Candida species isolated from patients with candidemia, and to assess their relationship with Candida genotypes derived after repetitive sequence-based polymerase chain reaction (rep-PCR) fingerprinting. Methodology: Fifty-two strains were identified to species level according to conventional methods and sequencing. The DiversiLab system was used for the genotyping. Enzyme activities and biofilm formation were evaluated using microbiological methods. Results: The 52 strains were identified as follows: 29 C. parapsilosis, 19 C. albicans, 2 C. glabrata, and 2 C. tropicalis. Phospholipase and proteinase activities were observed to have statistically significant differences between C. albicans and non-albicans Candida (NAC) strains (p < 0.05), with C. albicans strains showing higher virulence. Rep-PCR revealed eight major genotypes (A-H).The 19 C. albicans and the 33 non-albicans Candida isolates yielded seven (A-G) and four (A, B, C, H) genotypes, respectively. C. albicans strains were not shown to have a predominant genotype and showed higher phospholipase and proteinase activitiy than did NAC, regardless of genotype. Genotype H (52%) was the predominant genotype for the NAC including 27 C. parapsilosis strains, but the majority of strains showed low virulence. Conclusions: NAC species were the most common causative agent for candidemia. Genotyping showed low transmission of C. albicans strains, but transmission of C. parapsilosis was high. In candidemia, several Candida virulence factors may be responsible at the same time. However, different genotypes of Candida strains showed different virulence activity.